Reduction in the structural instability of cloned eukaryotic tandem-repeat DNA by low-temperature culturing of host bacteria - THAPANA, WATCHARAPORN (Genet Res (Camb), 2014)
For accurate analyses of eukaryotic tandem-repeat DNA, it is often required to clone a genomic DNA fragment into a bacterial plasmid. It is, however, a serious problem that tandem-repeat DNA is frequently subjected to structural changes during maintenance or amplification in the host bacteria. Here, we show an example of a clear difference in the instability of tandem-repeat DNA between different culturing temperatures. A fragment of monkey centromeric DNA carried by pUC19 was considerably degraded by culturing bacteria at 37 °C, but the damage was reduced at 25 °C. Thus, culturing temperature is a significant factor for avoiding degradation, in addition to the genotype of the host bacteria.